1993
DOI: 10.2175/wer.65.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and mean cell residence time on biological nutrient removal processes

Abstract: The effects of temperature and mean cell residence time (MCRT) on biological nitrogen and phosphorus removal were investigated by operating two pilot‐scale continuous‐flow reactors in parallel over a range of temperatures and MCRTs. One system was operated as a high‐rate Virginia Initiative Plant (VIP) biological nutrient removal (BNR) process, and the other was operated as a conventional, fully aerobic activated sludge process for comparison. Results showed that less aerobic volume was needed for complete nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 2 publications
4
26
0
Order By: Relevance
“…Because stored polyphosphate and cations, mainly potassium and magnesium, were measured as MLSS, it was expected that lower MLVSS/MLSS ratios would be observed as the amount of P increased in the sludge. McClintock 18 reported an MLVSS/MLSS ratio of approximately 70% in a system with high amounts of P in the sludge (>10% P/VSS), and a ratio of 80% or greater in a system with low amounts of P in the sludge (<4% P/VSS).…”
Section: Effect Of C/p Ratio On Nitrogen Removal Efficiencymentioning
confidence: 99%
“…Because stored polyphosphate and cations, mainly potassium and magnesium, were measured as MLSS, it was expected that lower MLVSS/MLSS ratios would be observed as the amount of P increased in the sludge. McClintock 18 reported an MLVSS/MLSS ratio of approximately 70% in a system with high amounts of P in the sludge (>10% P/VSS), and a ratio of 80% or greater in a system with low amounts of P in the sludge (<4% P/VSS).…”
Section: Effect Of C/p Ratio On Nitrogen Removal Efficiencymentioning
confidence: 99%
“…However, the results were inconsistent due to non-comparable experimental designs. Low temperature was reported to have an adverse impact on BPR efficiency (McClintock et al 1991;Mamais et al 1992). In other studies (Krichten et al 1985;Vinconneau et al 1985), better BPR was observed at lower temperatures (5 o C) than at higher temperatures (10 and 15 o C).…”
Section: Effect Of Temperaturementioning
confidence: 86%
“…The average reactor temperature for the period was about 17.5 o C. Using the EPA (1993) recommended temperature correction equation for nitrification, the specific nitrification rate at 20 o C can be calculated as 2.2 mg N/g VSS/hr. At an aeration SRT of 6.8 days, this specific nitrification rate is located on the curve presented by McClintock et al (1993).…”
Section: Nitrification and Nitrogen Removalmentioning
confidence: 93%